A review of the Stigmatophora palmata (Moore, 1878) species-group (Lepidoptera: Erebidae: Arctiinae) with description of a new species from China - Volynkin, Anton V.; Huang, Si-Yao; Dubatolov, Vladimir V. (Zootaxa, 2021)
The Stigmatophora palmata (Moore, 1878) species-group is reviewed. A new species, S. danieli Volynkin, S. -Y. Huang & Dubatolov, sp. nov. is described for the Chinese populations previously identified by authors as S. palmata. Stigmatophora palmata form inanis Seitz, 1913 is upgraded to species level: S. inanis Seitz, 1913, stat. nov. A new synonymy is established: S. inanis Seitz, 1913 = S. palliduspalmata N. Singh, Kirti & Joshi, 2016, syn. nov. A lectotype for Lyclene palmata Moore, 1878 is designated. The distribution patterns of S. palmata and S. hainanensis Fang, 1991 are clarified. Adults and male and female genitalia of all species are illustrated.